Evaluation of Arsenic, Cadmium, Lead and Mercury Contamination in Over-the-Counter Available Dry Dog Foods With Different Animal Ingredients (Red Meat, Poultry, and Fish) - Kim, Hyun-Tae; Loftus, John P.; Mann, Sabine; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2018)
Objectives: To examine the relative levels of heavy metals and arsenic content in commercial dog foods (arsenic, cadmium, lead and mercury) of 51 over-the-counter maintenance or all-life-stage dry dog foods. All products were chosen and segregated based on meat sources (fish, poultry, red-meat – 17 products from each category) as animal protein sources being the primary contaminated ingredient due to bioaccumulation. Methods: Inductively coupled plasma mass spectrometry (ICP-MS) was performed on products that were classified as fish, red meat (beef, pork, venison, bison) or poultry (chicken, turkey, duck) based. A non-Gaussian data distribution for each heavy metal within category distribution led to non-parametric statistical testing and median (range) descriptive statistics. Comparison to average human consumption based on mg/Mcal was also examined. Results: Based on caloric consumption, total arsenic and heavy metal consumption is higher in dogs than in humans; however chronic toxic exposure levels are highly unlikely. Fish-based diets had significantly higher arsenic, cadmium and mercury content than the poultry or red meat-based diets (p<0.01). Red meat-based diets (beef, venison and bison) had higher lead concentrations than poultry and fish-based diets (p<0.03). Clinical Significance: Based on the findings, commercial dog foods appear to be safe for chronic consumption and concentrations of the heavy metals were dependent on primary protein sources. Overall, poultry-based diets had relatively lower heavy metal and arsenic content than red meat and fish-based diets. Despite the safety of most pet foods occasional outliers for lead render some concern for chronic exposure based on other species toxicity data and a lack of data in dogs.